PENGARUH TERAPI JUS PEMENGKUR (PEPAYA MENGKAL DAN KURMA) TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS BELAKANG SOYA. - Yesti Ririhena; Abdul Thalib (Pasapua Health Journal, 2019)
Introduction : Hypertension is a common problem in the community so that many people are addicted to medical drugs which will certainly have a bad impact on their body. Efforts are being made to shift the habit of consuming medical drugs towards complementary medicine, one of which is with pemangkur-juice. Method: The research used was a pre-experimental design with one group pretest-posttest design.The sample of this study was selected using a non- probability sampling technique with a purposive sampling (n =49, α =0,005). Results: There is an effect of pemangkur- juice to reduction of blood pressure in hypertensive patients in Soya Public Health Center (р = 0,000). Conclusion: Pemangkur-Juice can be as one of complementary therapy for reducing blood pressure in patient hypertension.